From silos to systems : reframing schools for success - Kilgore, Sally (Corwin, 2011)
There may be multiple factors surrounding student absenteeism but few administrators have the luxury of investigating them all. This book provides specific application steps for engaging all staf in a systematic approach to dealing with the various casues of schoolwide problems.